2023
DOI: 10.1111/acv.12894
|View full text |Cite
|
Sign up to set email alerts
|

Combining species distribution models and moderate resolution satellite information to guide conservation programs for reticulated giraffe

Abstract: The conservation of threatened and rare species in remote areas often presents two challenges: there may be unknown populations that have not yet been documented and there is a need to identify suitable habitat to translocate individuals and help populations recover. This is the case of the reticulated giraffe (Giraffa reticulata), a species of high conservation priority for which: (a) there may be unknown populations in remote areas, and (b) detailed maps of suitable habitat available within its range are lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…GEE, is a cloud geospatial processing platform on Google computational infrastructure, used in different studies with spatial and temporal scales ( Gorelick et al, 2017 ). This platform has been used in studies exploring vegetation succession ( Adagbasa & Mukwada, 2022 ), species distribution ( Crego, Stabach & Connette, 2022 ; Crego et al, 2023 ), and to characterize large landscapes ( Rippel et al, 2023 ). GEE has been also used to map deforestation and forest degradation ( Shimizu et al, 2022 ; Wimberly et al, 2022 ), predict effects of climate change ( Workie & Debella, 2018 ; Shiff, Lensky & Bonfil, 2021 ), assess the impacts of wildfires ( dos Santos et al, 2023 ; Parra et al, 2023 ), and detect changes in land use and land cover ( Phan, Kuch & Lehnert, 2020 ; Tassi et al, 2021 ; González-González, Clerici & Quesada, 2022 ; Biswas et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…GEE, is a cloud geospatial processing platform on Google computational infrastructure, used in different studies with spatial and temporal scales ( Gorelick et al, 2017 ). This platform has been used in studies exploring vegetation succession ( Adagbasa & Mukwada, 2022 ), species distribution ( Crego, Stabach & Connette, 2022 ; Crego et al, 2023 ), and to characterize large landscapes ( Rippel et al, 2023 ). GEE has been also used to map deforestation and forest degradation ( Shimizu et al, 2022 ; Wimberly et al, 2022 ), predict effects of climate change ( Workie & Debella, 2018 ; Shiff, Lensky & Bonfil, 2021 ), assess the impacts of wildfires ( dos Santos et al, 2023 ; Parra et al, 2023 ), and detect changes in land use and land cover ( Phan, Kuch & Lehnert, 2020 ; Tassi et al, 2021 ; González-González, Clerici & Quesada, 2022 ; Biswas et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…We included elevation and surface roughness as terrain characteristics that are important drivers of habitat selection for large herbivores (Killeen et al, 2014), specifically for giraffes (Crego et al, 2023;Kimuyu et al, 2021). We obtained elevation data from the Shuttle Radar Topography Mission (SRTM) at 30 m resolution (Hennig et al, 2001).…”
Section: Environmental Variables and Model Predictorsmentioning
confidence: 99%
“…To standardize predictor resolutions (Deneu et al, 2022), all seven predictors were resampled to the 250 m pixel resolution using the default near neighbor method in GEE (see Appendix S1: Figures S1-S6). We checked that predictors were not highly correlated using Pearson test of correlation (r > 0.7); however, we retained the HH and HV bands although they were highly correlated (r = 0.9) as they provide different polarization bands (Santoro et al, 2009;Shimada et al, 2014;Yu & Saatchi, 2016) to the model prediction and have been observed to have varying influence on model predictions in other giraffe species (Crego et al, 2023). All spatial data processing was done in GEE, following the framework of Crego et al (2022).…”
Section: Environmental Variables and Model Predictorsmentioning
confidence: 99%
See 2 more Smart Citations